The genesis of poetic prose in the works of Louis-Ferdinand Celine through the transgressive and maieutic agency of the figure of the Double - Collett, Anne Elizabeth (French Language and Literature, 2024)
This study examines Louis-Ferdinand Celine's quest for the actualization of his creative aesthetic through the transgressive and maieutic agency of the figure of the Double manifest in his works. In that capacity, we examine the Double's role as a vehicle for the production of the author's poetic prose. To this end, we interrogate the role of the Double as a coping mechanism for the author's fractured psyche caused by the trauma of his war experiences and a concomitant horror Celine perceived as extant in man's inhumanity to man, concealed by a veneer of 'civilised' behaviour. Because the figure of the Double is manifest in Celine's works in two distinct capacities, both as a coping mechanism and in providing the impetus for the production of his poetic prose, we have divided this study into two sections comprising Transgressors and Midwives. The first analyses those elements in Celine's aesthetic which were transgressive, iconoclastic, providing the initial impulse for creative production. These influences include war and the author's concept of death; father figures who exerted an influence on both the medical and literary careers of the author; Celine's transgressive use of idiolect, and the presence in the author's work of Dionysian and Apollinian elements as a metaphor for creative conflict. The second section examines those aspects of the Double which are maieutic in the Socratic sense in that they deliver the outcome of dialectic argument present in the fundamental conflictual (and creative) opposition or rivalry between Doubles as a product of that dissent, in the form of poetic prose. Those elements which act as 'Midwives' in this context include the act of writing per seas a catalyst for the resolution of Celine's fragmented psyche; ambiguity and the grotesque in subterranean spaces as a site ofregeneration and finally, Shakespeare's works as an intertextual touchstone and seat of linguistic and poetic inspiration. If the word 'maieutic' relates to the Socratic method or dialectic of eliciting knowledge by a series of questions and answers, we posit that Celine's figurative use of a maieutic method for eliciting truth or authenticity in his work is evidenced in the high level of poetic prose as its outcome. It is also extant in the effect that the author's prose has on the reader in eliciting an active response in the form of a participatory reading of Celine's works by appealing directly to the reader's emotions as well as, in a best-case scenario, prompting the reader to re-write Celine's works. An observation of the trajectory of the figure of the Double throughout Celine's oeuvre, from his first manifestation in the person of the author's avowed double Bardamu 1 in tandem with the protagonist's Double Robinson in Voyage au bout de la nuit, t~ough the gradual decline of his avatars in successive novels, culminating in his final elimination in Celine's last work Rigodon, revealed a significant pattern in terms of a literary solution to a personal issue. We discovered a parallel between the novels in which the highest degree of poetic prose was attained and the presence of those figures of the Double who were most transgressive: Mille-Pattes in Guignol 's Band and Jules in F eerie pour une autre fois. We also noted that a relative diminution in the level of poetic prose in the novels of the trilogy coincided with a decline and eventual demise of the figure of the Double. This led us to conclude that the figure of the Double was simply a literary device for the actualization of the author's project: the resolution of Celine's internal conflict and his reliance on the Double as a seat of both refuge and inspiration, and a concomitant manifestation of an authentic voice represented in his poetic prose. However, we emphasise that the disappearance of the figure of the Double in Celine's works does not imply an abolition of that figure, but rather an assimilation by the protagonist of all those elements which constituted his 'Otherness'. This factor is inherent in the attainment of a state of immanence, both by Celine and the protagonists in his novels.